OBSTACLES TO STUDENTS' PRODUCTIVE CONNECTIVE THINKING IN SOLVING MATHEMATICAL PROBLEMS - Tasni, Nurfaida; Nusantara, Toto; Hidayanto, Erry; Sisworo, Sisworo; Susanti, Elly (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Students ability in making mathematical connection is one of the key goals in mathematics education. This study describes obstacles to students’ productive connective thinking in solving mathematical problems. Obstacles experienced by the students when solving mathematical problems were identified based on connective thinking networks completeness according to Thosio’s thinking scheme. Think aloud protocol worksheet and recording were analyzed descriptively. In solving mathematical problems, students faced obstacles in every thinking stage. They were unable to make a complete connective thinking network in cognition, formulation, reconstruction, and inference stage.